Single-session video and electromyography feedback in overhead athletes with Scapular dyskinesis and impingement syndrome - Du, W.-Y.; Huang, T.-S.; Chiu, Y.-C.; Mao, S.-J.; Hung, L.-W.; Liu, M.-F.; Yang, J. L.; Lin, J. J. (Journal of Athletic Training, 2020)
Context: Subacromial impingement syndrome (SIS) is associated with scapular dyskinesis, or imbalanced scapular muscle activity. Evidence has shown that feedback can improve scapular control in patients with SIS. However, it is unknown whether real-time video feedback or electromyography (EMG) biofeedback is optimal for improving scapular kinematics and muscle activity during a functional task. Objective: To compare the effects of video and EMG feedback sessions on absolute muscle activity (upper trapezius [UT], lower trapezius [LT], serratus anterior), muscle balance ratios (UT/LT, UT/serratus anterior), and scapular kinematics (anterior-posterior tilt, external-internal rotation, upward rotation) in SIS participants during arm elevation and lowering. Design: Randomized controlled clinical trial. Setting: Research laboratory. Patients or Other Participants: Overhead athletes who were diagnosed with SIS and who also exhibited scapular dyskinesis (N = 41). Main Outcome Measure(s): Three-dimensional kinematics and EMG were recorded before and after feedback training. Results: Lower trapezius muscle activity increased (4.2%-18%, P < .011) and UT/LT decreased (0.56-1.17, P < .013) in the EMG biofeedback training group as compared with those in the video feedback training group. Scapular upward rotation during arm elevation was higher in the video group than in the EMG group after feedback training (2.3°, P = .024). Conclusions: The EMG biofeedback improved muscle control and video feedback improved the correction of scapular upward rotation in patients with SIS.